Increasing Interest And Learning Outcomes In Learning Basic Of Industrial Chemical Engineering Using Natural Materials In The Environment Through Experimental Method For Students Of Class X TKI 2 SMK Negeri 3 Kendal Semester 1 Academic Year 2022/2023 - Nova Dyah Wulanningtyas (UJoST- Universal Journal of Science and Technology, 2022)
This study aims to increase interest and learning outcomes of the Basics of Industrial Chemical Engineering through the application of experimental methods in class X TKI 2 SMK Negeri 3 Kendal. The problems posed in this study are: Is the application of the experimental method in learning the Basics of Industrial Chemical Engineering using natural materials in the surrounding environment can increase student interest and learning outcomes in class X TKI 2 SMK Negeri 3 Kendal?". This study uses an action research method which is divided into two cycles, where each cycle consists of four stages, namely:1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. In this study, the researcher acted as a teacher in class X TKI 2 SMK Negeri 3 Kendal. Based on the results of the study, it can be concluded that the learning outcomes of Chemistry at SMK Negeri 3 Kendal can be improved by applying the experimental method. It is evident from the assessment of the student group that there is an increase in learning interest in cycle 1, namely 86.49% and in cycle 2, namely 100%. In addition to an increase in interest in learning, it is also proven that there is an increase in learning outcomes from cycle 1 with an average score of 86.44% and in cycle 2 the average value reaches 100%. This experimental method can be implemented by the Basics of Industrial Chemical Engineering teacher because it can increase student interest and learning outcomes, and change students' thinking that Basics of Industrial Chemical Engineering is boring and a difficult subject.